Spreading (Dis)Trust: Covid-19 Misinformation and Government Intervention in Italy - Alessandro Lovari (Media and Communication, 2020)
The commentary focuses on the spread of Covid-19 misinformation in Italy, highlighting the dynamics that have impacted on its pandemic communication. Italy has recently been affected by a progressive erosion of trust in public institutions and a general state of information crisis regarding matters of health and science. In this context, the politicization of health issues and a growing use of social media to confront the Coronavirus “infodemic” have led the Italian Ministry of Health to play a strategic role in using its official Facebook page to mitigate the spread of misinformation and to offer updates to online publics. Despite this prompt intervention, which increased the visibility and reliability of public health communication, coordinated efforts involving different institutions, media and digital platform companies still seem necessary to reduce the impact of misinformation, as using a multichannel strategy helps avoid increasing social and technological disparities at a time of crisis.